2010
DOI: 10.1021/cn100010p
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drugs Activate the C. elegans Akt Pathway via the DAF-2 Insulin/IGF-1 Receptor

Abstract: The molecular modes of action of antipsychotic drugs are poorly understood beyond their effects at the dopamine D2 receptor. Previous studies have placed Akt signaling downstream of D2 dopamine receptors, and recent data have suggested an association between psychotic illnesses and defective Akt signaling. To characterize the effect of antipsychotic drugs on the Akt pathway, we used the model organism C. elegans, a simple system where the Akt/forkhead box O transcription factor (FOXO) pathway has been well cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 65 publications
4
33
0
Order By: Relevance
“…The neurotransmitter and drug concentrations evaluated in these experiments were based on either standard values from the literature or levels found effective for other drugs of the same general class [24,25]. The drug and control plates were allowed to dry and equilibrate for 2-3 h prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…The neurotransmitter and drug concentrations evaluated in these experiments were based on either standard values from the literature or levels found effective for other drugs of the same general class [24,25]. The drug and control plates were allowed to dry and equilibrate for 2-3 h prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies of clozapine revealed that it binds to the trace amine-associated receptor TAAR1, which was then implicated in clozapine enhancement of PPI [56]. Moreover, two independent groups simultaneously identified the IIS pathway in C. elegans as a physiologically relevant target of a wide variety of antipsychotic drugs [57,58]. This work discovered a novel mechanism for coactivation of the insulin receptor and identified a potential mechanism by which clozapine may induce diabetes insipidus and hypertension [59].…”
Section: Psychiatric Drugs In C Elegansmentioning
confidence: 99%
“…Recent discoveries indicate a role for FoxO in the pathogenesis of depression and other psychiatric disorders (Polter et al, 2009;Weeks et al, 2010;Zheng et al, 2013). Enhanced neurotrophins or serotonin neurotransmission in animal brain phosphorylate and inactivate FoxO3a (Zheng et al, 2002;Polter et al, 2009).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%